2002
DOI: 10.1053/jhep.2002.35342
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of E-cadherin in hepatocellular carcinoma: Correlations with genetic alterations, β-catenin expression, and clinical features

Abstract: H epatocellular carcinoma (HCC) is one of the most common malignancies and a leading cause of death by cancer worldwide. Epidemiologic studies have shown that more than 70% of HCC cases are linked to chronic infection with hepatitis B virus (HBV) or hepatitis C virus (HCV). Other risk factors include alcohol-related cirrhosis, dietary intake of aflatoxin B1 in some tropical areas, and inherited metabolic disorders such as tyrosinemia, hemochromatosis, and ␣1-antitrypsin deficiency. Recent insights into the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 46 publications
12
118
4
Order By: Relevance
“…Immunohistochemical analysis of E-cadherin expression in TMA including 125 HCCs tissues revealed obvious variations among tumor samples, ranging from complete or heterogeneous downregulation in 42.4% of cases to striking overexpression in 34.4% of tumors, which was similar to the results of Buendia's (Wei et al, 2002), and E-cadherin level in cytoplasm was not associated with OS too. Different from the membrane and cytoplasm alone, we considered both factors in coming and found the high membrane/ cytoplasm ratio was an independence prognostic factor.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Immunohistochemical analysis of E-cadherin expression in TMA including 125 HCCs tissues revealed obvious variations among tumor samples, ranging from complete or heterogeneous downregulation in 42.4% of cases to striking overexpression in 34.4% of tumors, which was similar to the results of Buendia's (Wei et al, 2002), and E-cadherin level in cytoplasm was not associated with OS too. Different from the membrane and cytoplasm alone, we considered both factors in coming and found the high membrane/ cytoplasm ratio was an independence prognostic factor.…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that liver metastases of gastric tumors are composed strongly E-cadherin-positive cells during outgrowth in the liver environment (Mayer et al, 1993). E-cadhrin can also promote lymphovascular and intraepithelial invasion in other tumor types, enforced intercellular adhesion mediated by E-cadherin might favor the intake and expansion of tumor cells in liver and the shift of E-cadherin between membrane and cytoplasm may be associated with metabolite and functional changes of E-cadherin (Wei et al, 2002). To gain further insight into E-cadherin involvement of in HCC, we use immunohistochemistry to examine the levels of E-cadherin expression in 125 primary HCC samples.…”
Section: Altered Distribution and Expression Pattern Of E-cadherin Inmentioning
confidence: 99%
“…In addition, an inverse correlation between E-cadherin expression and Snail expression had been found in a previous study using HCC cell lines; however, no association was found between the two gene expressions in the 47 HCC and eight NIN tissue samples in this study. Several reports have shown two mechanisms in the downregulation of E-cadherin in HCC; one is the hypermethylation of the E-cadherin promoter and the other is the loss of heterozygosity of the E-cadherin gene (Kanai et al, 1997;Matsumura et al, 2001;Wei et al, 2002). The authors demonstrated that DNA hypermethylation of the Ecadherin promoter region was observed in 33 -67% and loss of heterozygosity (LOH) was detected in 30 -43% of HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated expression of E-cadherin is common in HCC, with promoter methylation observed early in hepatocarcinogenesis, while LOH of the E-cadherin locus is common during tumor progression (Kanai et al, 1997(Kanai et al, , 2000. The findings that downregulation of E-cadherin is associated with chronic HBV infection (Wei et al, 2002), that HBxAg promotes cell migration (Lara-Pezzi et al, 2001a, b) and reduces cell adhesion (Lian et al, 2003), suggest that HBxAg may downregulate E-cadherin. The inverse correlation between HBxAg and E-cadherin in tissue culture cells (Figure 2) and in tumor/nontumor tissues (Figure 3), and that HBxAg promotes E-cadherin promoter methylation (Figure 4), support the hypothesis that HBxAg targets E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…A major E-cadherin-binding protein, b-catenin, plays a critical role in Wnt signaling and in tumorigenesis (Wei et al, 2002). E-cadherin-binding sequesters b-catenin to the cell membrane, where b-catenin signaling is inhibited (Gottardi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%